Transfusion Related transmission of infections among blood donors of South Punjab - Samiullah; Rasheed, Ammara; Saleem, Umera; Ijaz, Amrat (Journal of Rawalpindi Medical College, 2022)
Objective: To investigate the frequency of blood transmissible infections in the region of South Punjab. Study design: Descriptive cross-sectional Place and duration: Study was carried out from February 2019 to February 2021 over a period of 2 years at—removed for blind review–. Methodology: All voluntary and replacement donors who arrived at the hospital between the included time period were considered for the analysis. Total two blood samples were taken from each blood donor. For blood grouping and malarial parasite screening, Ethylene diamine tetra acetic acid (EDTA) sample was collected. Clotted sample was used for screening of Anti-HCV, HBsAg, HIV and syphilis and analyzed by ELISA. Results: Our study showed cumulative frequency of 0.8 %, 0.5% and 1% for hepatitis B, syphilis and C virus respectively, and only one case of HIV and malarial parasite observed during screening for blood transfusion among blood donors. Conclusion: Increasing transmission prevalence of hepatitis as well as syphilis in our region. Keywords: blood transfusion, infection, HBsAG, HCV.